MULTIPLIKASI TUNAS MELINJO (GNETUM GNEMON) SECARA INVITRO - Rossa Yunita (Jurnal Sagu, 2004)
An experiment has been done at Laboratorium TLs.suc Culture of "Balai Penelitian Bioteknologi danGenctik Pertanian", Bogor, starting on July 2001 until June 2(M)2. The objective of the research is to studymultiplication of melinjo bud (Gnetum gnemon) by using in vitro technique. The experiment used factorialcomplete randomized design witli 19 replications. The thidiazuron were used as treatments at the concentra-tion of 0; 0,1 and 03 Ppm in combination with three kinds of medium i.e. MS, WPM and Anderson. The resultshowed that treatment of melinjo bud thidiazuron 0,3 ppra in MS medium could increase number of budmultiplication.